2021
DOI: 10.22540/jfsf-06-139
|View full text |Cite
|
Sign up to set email alerts
|

Physical function measurement in older long-term cancer survivors

Abstract: Objective: To establish reliability, validity, and minimal detectable change in measures of function in older long-term cancer survivors. Methods: Older cancer survivors were recruited to perform functional measures; 5 Times Sit-to-Stand (5xSTS), 30-second Timed Chair Rise (30sTCR), Short Physical Performance Battery (SPPB), Physical Performance Test-7 (PPT-7). Two testing sessions were completed two weeks apart. Test-retest reliability was examined using the intraclass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
1
10
1
Order By: Relevance
“…In this study, we reported data on the subjective and objective measures of physical function among Hispanic women with breast cancer. We found that some measures of physical function such as TUG and 4SB were worse in Hispanics, while PROMIS-PF score, PROMIS-F score, STS, and GS were comparable to women of other race/ethnicity with breast cancer, as reported in the literature (Blackwood & Rybicki, 2021a, 2021bMatthys et al, 2021;Van der Weijden-Van Doornik et al, 2017). In addition, we also found that one in every five patients in our sample had depression.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, we reported data on the subjective and objective measures of physical function among Hispanic women with breast cancer. We found that some measures of physical function such as TUG and 4SB were worse in Hispanics, while PROMIS-PF score, PROMIS-F score, STS, and GS were comparable to women of other race/ethnicity with breast cancer, as reported in the literature (Blackwood & Rybicki, 2021a, 2021bMatthys et al, 2021;Van der Weijden-Van Doornik et al, 2017). In addition, we also found that one in every five patients in our sample had depression.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, the mean GS was 19.0 kg. These values were below the mean reported value of 27.7 kg for healthy adults with ages between 50 and 59 years (Blackwood & Rybicki, 2021b; Van der Weijden-Van Doornik et al, 2017). A decrease in GS for women with breast cancer treated with aromatase inhibitors has also been reported with a range between 0.1% and 9.7% (Van der Weijden-Van Doornik et al, 2017).…”
Section: Discussioncontrasting
confidence: 80%
“…Cancer survivors are at higher risk for physical function limitations compared to individuals without a history of cancer based on patient‐reported measures 6,13,14 . While patient‐reported physical function measures are important for understanding the lived experience of survivorship, objective physical function assessments are valid and reliable measures that can identify impairments amenable to rehabilitation interventions 15 . Prior studies that included objective measures of physical function focused on breast and prostate cancer survivors to the exclusion of other cancer types, with mixed findings regarding the presence of physical functional limitations 16–18 .…”
Section: Introductionmentioning
confidence: 99%
“…6,13,14 While patient-reported physical function measures are important for understanding the lived experience of survivorship, objective physical function assessments are valid and reliable measures that can identify impairments amenable to rehabilitation interventions. 15 Prior studies that included objective measures of physical function focused on breast and prostate cancer survivors to the exclusion of other cancer types, with mixed findings regarding the presence of physical functional limitations. [16][17][18] Although breast and prostate are the most common cancer types, less is known about physical function in older adults with other cancer types and how physical function impairments might differ between men and women with a cancer history.…”
Section: Introductionmentioning
confidence: 99%
“…The CGA has historically been adopted to identify elderly patients who are unfit for intense oncologic treatment, but is time-consuming and therefore costly. Next to a geriatric assessment, specific physical function in older adults can be assessed by performance tests [ 13 ]. Timely identifying high-risk patients before the start of treatment is important to be able to initiate preventive interventions to improve treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%